BOX GIRDER BALANCE CANTILEVER CONSTRUCTION METHOD - DW. Hendro Kustarto (CI-TECH, 2021)
The apporach bridge whose construction is a continuous prestressed box girder is part of the Suramadu bridge as a link between the cause-way and the cable bridge (main span), and consists of two parts, namely the Surabaya side and the Madura side, each of which has the same geometric (symmetric)In the sequence of implementation, the Surabaya side is slightly different from the Madura side, where the Madura side still refers to the initial design, while the Surabaya side changes slightly with the aim of speeding up the implementation time. In principle, this change does not affect the strength, durability and safety of the construction, only limited to the issue of implementation time.The two approach bridges (Surabaya and Madura sides) consist of 2 parts, the first is a continuous box girder with a side span of 2 x 40.00 and a middle span of 7x 80.00m, the second is a V-pier with a span of 32.00 m. The balanced cantilever construction method is applied to eliminate these difficulties. To shorten the implementation time on the Surabaya side approach, that is by rearranging the sequences in such a way that there are several closures that are done simultaneously without reducing the strength of the structure specified in the initial design. As for the Surabaya side, there are changes for both the West and East sides, theoretically this change will save about 10 days, which is the length of time it takes to complete 1 closure. The final optimization of the Suramadu Approach bridge is with a span of 80 m between piers with a longitudinal slope of 4%, with a single cell box girder shape that will speed up execution and reduce the quantity of work and has a hollow shaped pillar. There are several closures carried out simultaneously on the approach bridge on the Surabaya side. This is done to speed up the implementation, considering that the Surabaya side is already behind the schedule.)